Tryphactothrips rutherfordi (Bagnall) (Thysanoptera, Panchaetothripinae): first description of the male - Tyagi, Kaomud; Singha, Devkant; Singha, Devkant; Pakrashi, Avas; Das, Moumita; Kumar, Vikas (Zootaxa, 2020)
The subfamily Panchaetothripinae (family Thripidae) is represented by 140 species under 40 genera (Thrips Wiki 2019). In India, 36 species under 16 genera are recorded (Tyagi & Kumar 2016, Tyagi et al. 2017, Rachana and Varatharajan, 2018, Johnson et al. 2019). The members of this subfamily are leaf-feeders and usually dark brown in colour with strongly reticulate sculpture on body, terminal antennal segments needle-shaped, tarsi 1- or 2-segmented, fore wing upper vein fused with costa. The genus Tryphactothrips was established by Bagnall (1919), and this genus remains monobasic with only Dinurothrips rutherfordi Bagnall from Sri Lanka as the type species. The genus Tryphactothrips can be distinguished from related genera by the presence of sculptured round areolae on abdominal segments. It is closely related to Anisopilothrips Stannard & Mitri but can be identified by paired sigmoidal setae on abdominal tergites (absent in Anisopilothrips), mesonotum without complete median longitudinal split (complete median longitudinal in Anisopilothrips). Recently, a series of both sexes of Tryphactothrips rutherfordi with banded fore wings was collected on fern from Kerala state of India. Females were identified using published keys (Wilson 1975), and the male is here described for the first time. DNA was isolated from the studied specimens and partial fragment of mtCOI gene was amplified and sequenced (Tyagi et al. 2017). Four sequences were submitted in the GenBank (Accession No. MN627201 to MN627204). Photographs and illustrations were taken through a Leica Trinocular Microscope (Leica DM-1000) using Leica software application suite (LAS EZ 2.1.0). The studied specimens were deposited in the National Zoological Collections (NZC), Zoological Survey of India, Kolkata, India.